ANALISIS PENGARUH KUALITAS PELAYANAN HARGA, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Lembaga Kursus Musik di Centro Course) - Osman, Feranda; Zamhari; Miranda, Lona (Jurnal Progresif Manajemen Bisnis, 2018)
The theories used in this research are Management theory, Marketing Management theory, Service Quality theory, Price and Promotion Theory, and Customer Satisfaction theory. The method used in this research is descriptive with a quantitative approach with the intention to find the correlation between an independent variable and a dependent variable by using a statistical formula that researches the relation of service quality, price, and promotion to customer satisfaction at the music institute of Centro Course. In addition, this study also aims to examine the relationship between service quality, price, and promotion to customer satisfaction in Centro Course. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The population in this research is the 45 customers at Centro Course. The sample in this study amounted to 45 people because if the subject of research carried less than 100 people, then it would be better to take all so that the research is a population study. The results of the study show that: (1) there is a significant influence between the quality of service to customer satisfaction. This is proved by the value of t-count> t-table (2.860> 2.01669). (2) The results also show that there is a significant influence between price and customer satisfaction. This is proved by the value of t-count> t-table (3.305> 2.01669). (3) The results show that there is a significant influence between promotion and customer satisfaction. This is proved by t-count> t-table (3,435> 2.01669). And (4) The result of research indicates that there is a significant influence on the variable of service quality, price, and promotion to customer satisfaction in Centro Course which is proved by Fcount (14,313)> Ftable (2,83).